Customer satisfaction toward local spices product Taman Perpaduan Ipoh / Mimi Shahira Wahida Che Lazim - Che Lazim, Mimi Shahira Wahida (Faculty of Business and Management, Universiti Teknologi MARA Cawangan Sarawak, 2015)
The purpose of this research is about factors that affect a customer satisfaction towards local spices product. The most importance point is to investigate about the relation with service quality, product quality and store attributes that influences customer satisfaction that leads for loyalty. The target respondents of this study were 100 of respondent who have come to our factory, and also people who attended our booth during promotion activities made by the company. The secondary data were used in this study to gain information. 100 sets of questionnaire have been distributed to the respondent. In this study, a researcher using a SPSS version 2.0 for analyse their data given by their respondents. This report represents about the introduction view, the literature review, research methodology, findings and their interpretations of data, a recommendations, a conclusions and also for a bibliography. Furthermore, most of these chapters with explained in detailed with their subs topic that discuss with the essential procedures and steps for completing these study. On this chapter will discuss about the background of study, scope of study, problem statement, objectives and research question, limitation and significance involved and also discusses the definition of the main terms used in this research.